Versehrung verstehen Fachwissenschaftliche und fachdidaktische Perspektiven auf physisches und psychisches Erleben in der Gegenwartsliteratur - Steffen, Röhrs; Söhnke, Post (Wissenschaftliche Buchgesellschaft (wbg), 2023)
The volume offers scientific and didactic perspectives on the relationship between injury and understanding in contemporary German literature. The multidimensional concept of disability can be used to describe a wide range of manifestations of illness, violence, mental disorders and traumatisation, with the phenomenon encompassing physical and psychological facets as well as social and cultural interactions. Literary representations of injury - according to the central assumption - have great potential both for an emphatic understanding of existential crises and for a critical analysis of complex issues. With contributions e.g. on Dorothea Dieckmann, Christian Duda, Hubert Fichte, Olga Grjasnowa, Elfriede Jelinek, Abbas Khider, Michael Kleeberg, Ingo Niermann, Inka Parei, Stephan Roiss, Kathrin Schmidt, Werner Schwab, WG Sebald, Alexander Wallasch, Daria Wilke, Mario Wirz and Juli Toe.